(untitled) (European Journal of Teaching and Education, 2022)
The global pandemic created by COVID-19 altered the landscape of education, creating the need for flexible methods of teaching and learning and a reliance on technology that many educators and students were not prepared for. Educators adapted their instructional methods to include shifts in pedagogy and the use of remote, hybrid, and flipped classrooms. Despite the additional preparation time, educators found themselves grappling with questions about creating inclusive communities for learners, decisions about how to meaningfully incorporate technology, and how to support student engagement. Without the presence of clear research and guidance, decisions such as whether students should be mandated to enable their cameras during class manifested. Educators were challenged to balance their obligations to assess learning with concerns about increasing equity gaps, access issues, and systemic challenges that are disproportionately experienced by marginalized learners. In an educational environment where video conferencing has become the norm, understanding how requiring camera use is experienced by students and educators and its role in supporting the classroom community is paramount. This study focused on students’ and educators’ perspectives of camera use in the classroom. Findings revealed that educators and students made sense of the utility of cameras, mandating camera use and their role in developing classroom communities differently. Students generally expressed their capacity to decide for themselves when camera use supported versus hindered their participation and appreciated practicing their agency. Educators generally understood camera use as central and necessary to building classroom community and assessing student involvement, participation, and understanding of class content.